Calagem, adubação orgânica e manejo da água no controle da toxicidade de ferro em arroz irrigado - Morel Freire , Francisco; Ferreira de Novais , Roberto; Soares, Plínio César; da Costa , Liovando Marciano; Alves Faria , Erpino (Revista Ceres, 2025)
Under greenhouse conditions, samples of a soil from a bottom land area in Muriaé County, State of Minas Gerais, previously incubated with 300 ppm of iron as FeCl3. 6H20, were submitted to treatments involving liming (4 t/ha); cattle manure (20 t/ha); rice straw (10 t/ha); flooding for 15 and 30 days before the transplanting of the seedlings; flooding at and 15 days after the transplanting time; absence of flooding for 7 days; and, flooding at the transplanting time with renewal of the water each 7 days.